Pemanfaatan Teh Rosela (Hibiscus Sabdariffa L) Sebagai Obat Tradisional Dalam Upaya Swamedikasi di Gampong Puuk Kecamatan Pidie Kabupaten Pidie - Dewi, Ervina; Agustina, Rahmi; Nur, Muhammad (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
Swamedikasi is a person's effort to treat illness or symptoms of illness by using certain plants. One of the plants that has been proven to have medicinal properties is the rosella (Hibiscus sabdariffa L). The objectives of this activity are: (1) Increasing knowledge of the relationship between health and well-being through self-medication efforts, (2) Empowering housewives to make traditional medicines, especially rosella tea, with the right formula, manufacturing method and dosage so that it is safe for consumption and efficacious. This activity was carried out using the Pre-Post Test Design method through counseling which was carried out on May 2-3, 2024 at the Keuchik Gampong Puuk office, Pidie District, Pidie Regency. The implementation of the Community Service program entitled: Utilization of Rosella Tea (Hibiscus sabdariffa L) as a Traditional Medicine in Self-medication Efforts in Gampong Puuk, Pidie District, Pidie Regency, Aceh Province went very well. The results of the activity show that this activity is able to: (1) Increase public knowledge of the importance of implementing a healthy lifestyle; (2) Introduce a self-medication program and make a health drink, namely rosella tea, with the right formula.